PRESBIKUSIS : Masalah Telinga pada Usia Tua - Rara Enggola Handayani; Baluqia Baluqia (Jurnal Anestesi, 2024)
Increasing age causes disorders in various organs due to degenerative processes. Presbycusis is one type of disorder that is most often experienced by the elderly group in the field of ENT. This hearing loss is bilateral progressive, irreversible and symmetrical neurosensory caused by cochlear degeneration. This condition cannot be cured, but several actions can be taken to improve the sufferer's quality of life, such as using hearing aids and cochlear implants.